Ontogenesis of Pelargonia sidoides (Geraniaceae) under greenhouse conditions - M. M. Gaidarzhy; A. V. Holubenko; N. V. Nuzhyna; O. A. Futorna; O. O. Senchylo (Regulatory Mechanisms in Biosystems, 2019)
The article presents the results of the ontogenesis study and complements the morphological description of the valuable medicinal plant Pelargonium sidoides, which is included in the Red List of Plants of South Africa, from the collection of succulents of the O. V. Fomin Botanical Garden. Unlike some species of the Pelargonium genus, which are stem succulents, P. sidoides is a succulent with thickened roots. It has been established that the pregenerative period lasts about 10 months, while the longest is the juvenile stage, during which plants form a large leafy series and begin to form thickened roots. The seedling stage in P. sidoides is much shorter than in many stem succulents with non-succulent leaves. Plants are cross-pollinated, in the conditions of cultivation they form a peduncle longer than in nature, up to 90 cm in length. Flowers are open to 6 days and during this time they undergo three consecutive stages: the opening of the anthers, an asexual pause, readiness of the pistil to be pollinated. Pollen grains are typical for representatives of the Pelargonium genus, but smaller, compared to pollen representatives of other sections. Fruits ripen in a short period 17–25 days, depending on the air temperature. The mericarps of P. sidoides differ in shape, colour and size from the mericarps of representatives of other genera of the Geraniaceae family, but the morphological characteristics of the seeds within the family are similar. The germ is located on the abdominal side of the seed; it occupies almost half of its volume and has clear outlines. According to its morphological features, P. sidoides leaves, as in most other species of the genus, have both mesomorphic and xeromorphic features. Analysis of the data gives ground for characterizing these plants as meso-xerophytes. P. sidoides quickly enters the generative period in the conditions of greenhouse cultivation and has high reproductive capacity.